First report of Sclerotium hydrophilum Sace causing stem rot disease of rice in Godavari zone of Andhra Pradesh - Dr. P. Ramanjineyulu; Dr. D. KRISHNAVENI; Dr. G.S. JASUDASU; Dr. S. SURESH RAO; Dr. E. RAJESWARI (ORYZA-An International Journal of Rice, 2026)
During the rainy season of September-October 2022, rice plants (cv. Swarna; MTU7029) in Pedapudi village, East Godavari district, Andhra Pradesh, exhibited brown to black, water-soaked lesions with irregular margins on the outer leaf sheaths near the waterline. The causal fungus was isolated on potato dextrose agar and produced abundant, initially white, round sclerotia that turned brown to black upon maturity. Microscopic examination revealed right-angled branching hyphae with slight constriction at the branch points; hyphal width ranged from 3.04 to 6.68 mm (mean 4.80 mm). Sclerotial diameter ranged from 0.26 to 0.49 mm (mean 0.39 mm). The internal transcribed spacer (ITS) region of the isolate was amplified and sequenced (GenBank accession ON514170), showing 99.83% nucleotide identity with Sclerotium hydrophilum strain SH1 (GenBank accession KX181457.1). Pathogenicity was confirmed on rice cultivar Prabhat (MTU3626) under glasshouse conditions, fulfilling Koch's postulates. Based on cultural, morphological, pathogenic, and molecular characteristics, the pathogen was identified as Sclerotium hydrophilum. According to existing literature, this constitutes the first confirmed report of S. hydrophilum causing stem rot of rice in the Godavari delta zone of Andhra Pradesh.